2014
DOI: 10.5539/ibr.v7n2p1
|View full text |Cite
|
Sign up to set email alerts
|

How are Different Slack Resources Translated into Firm Growth? Evidence from China

Abstract: This paper aims to clarify types of slack resources and mechanisms through which these resources are translated into the growth of transition economy firms. It compares human resource slack and financial slack in terms of their 'proactivity' to unveil their differing effects on firm growth. This paper further highlights firm-level entrepreneurial activities as a mechanism through which these resources are translated into firm growth. Data was collected from senior managers through a questionnaire survey from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
5
0
4
Order By: Relevance
“…A folga nanceira fornece às empresas a autonomia e recursos necessários para explorar novas oportunidades no mercado em que está inserida (Kim, Kim & Lee, 2008). Esta é uma espécie de proteção que a empresa tem ao disponibilizar novos recursos para a sua continuidade, já que o nanceiro não é estático e pode apresentar resultados negativos (Laffranchini & Braun, 2014;Dai & Kittilaksanawong, 2014).…”
Section: Referencial Teóricounclassified
See 1 more Smart Citation
“…A folga nanceira fornece às empresas a autonomia e recursos necessários para explorar novas oportunidades no mercado em que está inserida (Kim, Kim & Lee, 2008). Esta é uma espécie de proteção que a empresa tem ao disponibilizar novos recursos para a sua continuidade, já que o nanceiro não é estático e pode apresentar resultados negativos (Laffranchini & Braun, 2014;Dai & Kittilaksanawong, 2014).…”
Section: Referencial Teóricounclassified
“…A folga nanceira é representada pelos ativos líquidos que não estão aplicados a nenhuma atividade organizacional, o que a faz necessária para eventuais acontecimentos na empresa e de grande valia às nanças da organização (Dai & Kittilaksanawong, 2014). Esta análise faz-se importante principalmente para situações mais delicadas, como em casos de recessão, crise, expansão ou desenvolvimento de novos produtos, onde são necessários maiores ou menores níveis de recursos próprios (Namiki, 2012).…”
Section: Introductionunclassified
“…Through government funding subsidies or industryuniversity cooperation, HEIs' use of resources and knowledge can help improve their teaching, research, and service performance (Ryan, 2005;Dai and Kittilaksanawong, 2014;Veer Ramjeawon and Rowley, 2018;Findler et al, 2019). However, whether resource inputs can really achieve corresponding performance outcomes remains untested.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, due to the lack of educational resources on the market, HEIs cannot obtain enough of these (Khanna & Palepu, 2000); slack resources may represent a valuable, unique, and specific source that could have great impact on institutional performance. Ryan (2005) discussed the relationship between financial resources, institutional expenditures, and student engagement; he showed that only instructional expenditures have a significant influence on teaching and service performance (Dai & Kittilaksanawong, 2014). The first hypothesis of this study is:…”
Section: Isrmentioning
confidence: 99%
“…As the RBV has been widely used and developed in studies conducted on for-profit (Barney, 1991;Dai & Kittilaksanawong, 2014;Voss et al, 2008) and non-profit organizations Kraatz & Zajac, 2001), it can also help one understand the operation of HEIs for the following reasons.…”
Section: Resources Of Heismentioning
confidence: 99%